Case-based Learning Video and Learning Motivation among Midwifery Students - Ulfa Farrah Lisa; Feri Anita Wijayanti (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2023)
Case-based learning is commonly used in various settings, including the medical field. This study aims to determine the effect of case-based learning video on learning motivation among midwifery students. This was a quasi-experimental study with pre-test and post-test approach. This study was conducted at the Bachelor of midwifery study program, Faculty of Medicine, Andalas University from August to October 2021. Forty-nine student midwives were selected through total sampling technique. Demographic information and motivation data were collected using the Motivated Strategies for Learning Questionnaire (MSLQ). Descriptive statistics, ANOVA/Kruskal-Wallis test, and Paired T-Test/Wilcoxon Rank-sum test were applied to analyze the data. A p-value of less than 0.05 was considered statistically significant. This study reported no significant differences between age and the MSLQ value components. Nonetheless, significant differences were found between parents' income with intrinsic motivation (p equals 0.012), task value (p equals 0.044), and self-efficacy (p equals 0.02). Furthermore, there was a significant difference between intrinsic motivation and residence (p equals 0.012) among the other value components. The mean scores for all value components of motivation increased after the case-based learning video intervention. Two value components (task value and efficacy) showed a significant difference (p-value 0.026 and 0.000). In conclusion, case-based learning video effectively improved motivation among students. Such finding is essential to developing suitable learning method for students.